The Interrelation between Forced Eviction and the Right to Development - Ghiblartar, Difa; Handayani, Irawati (Padjadjaran Journal of International Law, 2019)
AbstractCountry?s development is one of the most common reason to evict inhabitant forcibly. This is because individuals or communities are often placed as objects in the development process and hence causing the closure of a room of their participation in such process. In the perspective of human rights, development is deemed as an individual right from which, every human being has the right to participate, contribute, and receive benefits of the result. This article aims to analyse the cases of forced evictions according to the right to development in Human Rights Law and sees how such right has been implemented as a state obligation at the national level. The study thus reveals that certain principles of the right to development, such as a holistic development, placing humans as the central subject of development,  as well as participation in the development process,  can sufficiently protect individuals and communities from the case of forced evictions. This article further argues that state plays significant role to ensure the fulfillment of the right to development.Keywords: Forced Eviction, Human Rights, Right to Development, State Obligation AbstrakPembangunan negara merupakan salah-satu alasan paling umum penyebab terjadinya penggusuran paksa. Hal ini dikarenakan individu atau masyarakat ditempatkan sebagai objek pembangunan yang menyebabkan tertutupnya ruang partisipatif dalam pembangunan tersebut. Dalam perspektif hak asasi manusia, pembangunan diklaim sebagai hak dimana setiap orang berhak untuk berpartisipasi, berkontribusi dan menerima manfaat hasil pembangunan. Penelitian ini bertujuan untuk mengetahui perspektif hak atas pembangunan terhadap penggusuran paksa, serta bagaimana kewajiban Negara dalam menerapkan hak tersebut ditingkat nasional. Berdasarkan analisis terhadap prinsip-prinsip dalam hak atas pembangunan seperti pembangunan yang holistik; penempatan manusia sebagai subjek sentral dari pembangunan dan juga partisipasi dalam proses pembangunan dapat melindungi individu atau masyarakat dari penggusuran paksa. Untuk menjamin pemenuhannya, Negara dalam menerapkan hak atas pembangunan ditingkat nasional.Kata Kunci: Hak Asasi Manusia, Hak atas Pembangunan, Penggusuran Paksa, Kewajiban Negara